Effect of self-care training program based on Orem's model on the behaviors leading to sexually transmitted disease in vulnerable women - Zahra Baghersad; Nasrollah Alimohammadi; Zahra Boroumandfar; Parastoo Golshiri (Wolters Kluwer Medknow Publications, 2016)
Background: Vulnerable women are prone to sexually transmitted diseases due to their high-risk behaviors. The present study aimed to investigate the effect of self-care training program based on Orem's model on the behaviors leading to sexually transmitted diseases in vulnerable women. Materials and Methods: This field trial was initially conducted on 100 women covered under health services and welfare organization in Isfahan city, who were selected by rationing ssampling. For needs assessment, they filled the self-care needs assessment questionnaire in three domains of knowledge, attitude, and practice. Then, at the stage of intervention (self-care training), 64 subjects were selected through convenient sampling and were assigned to experimental and control groups by random allocation. Data were analyzed by descriptive and analytical statistical tests through SPSS 18. Results: Results showed that mean scores of knowledge (P < 0.001), attitude (P < 0.001), practice (P = 0.04), and behavior change (P = 0.01) were significantly higher immediately after and 3 months after intervention, compared to before intervention, but there was no significant difference in mean scores between immediately after and 3 months after intervention. Conclusions: With regard to these results, it can be concluded that if the educational programs are planned based on clients' real needs assessment, the learners follow the educational materials, related to their problems, more seriously and it results in a notable behavior change in them.